K Kajian Deskripsi Semiotika Pada Pakaian Khas Kediri - Widiatmoko, Sigit; Budiono, Heru; Wiratama, Nara Setya; Sasmita, Gusti Garnis (PINUS: Jurnal Penelitian Inovasi Pembelajaran, 2022)
Traditional clothing as a form of regional identity and pride deserves the attention of all parties, both government, practitioners, academics and society. One of the special clothes that is interesting to study is the typical clothes of Kediri. This study has the objectives: (1) to describe the data sources for studying typical Kediri clothing, (2) to identify the types of typical Kediri clothing, and (3) to understand the values ​​contained in typical Kediri clothing. In conducting research, researchers used semiotic induction description method with a qualitative approach. The data sources for studying Kaḍiri clothing can refer to several historical data sources, traditional values ​​or ethnoarchaeology, such as from inscriptions, statues, reliefs, literature, and ethnoarchaeological evidence. Based on the data sources that have been obtained by the researchers, two types of clothing were born, namely Wḍihan Kaḍiri for men's clothing and Ken Kaḍiri for women's clothing. This typical Kediri dress also has noble values ​​which are its trademark, namely religious values, cultural values, historical values, social values, aesthetic values, ethical values, and economic values.